3D-printing aided resection of intratracheal adenoid cystic carcinoma and mediastinal mature cystic teratoma in a 26-year-old female: a case report - Lu, Di (J Thorac Dis, 2018)
Complete resection remains the ideal treatment for most patients with primary intratracheal tumors. Due to the limit in the resection length, the localization of the tumor during the surgery could be rather difficult if it hasn’t invaded out of the trachea, which might be more difficult when there’s another tumor in the anterior mediastinum. A 26-year-old woman with intratracheal adenoid cystic carcinoma (ACC) presented with dyspnea. CT scan revealed not only an ACC without extension out of trachea, but also a mediastinal teratoma (MT) near aorta, making the operation much more complicated than usual. To solve this problem, 3D-printing was applied for facilitating surgery plan making and intraoperative locating of ACC. And as we expected, the operation went successfully and the patient achieved full recovery without complications. To the best of our knowledge, the case of both intratracheal ACC and MT in one patient has not been previously reported.